Usefulness of laboratory and radiological investigations in the management of supraventricular tachycardia. (20th March 2017) - Ashok, Aadith; Cabalag, Miguel; Taylor, David McD
Abstract: Objective: Although ED patients presenting with supraventricular tachycardia (SVT) are commonly investigated, the value of these investigations has been questioned. We aimed to determine the frequency and utility of investigations in patients with SVT. Methods: We undertook an explicit retrospective medical record audit of patients with SVT who presented to a single ED (January 2004 to June 2014). Data on demographics, presenting complaints, investigations and outcomes were extracted. The outcomes were nature and utility of investigations. Results: A total of 633 patients were enrolled (mean [SD] age 55.4 [17.7] years, 62% female). Laboratory investigations were common: electrolytes (83.7% of patients), full blood count (81.2%), magnesium (57.5%), calcium (39.3%) and thyroid function (30.3%). These investigations revealed many mildly abnormal results but resulted in electrolyte supplementation in only 19 patients: eight with mild hypokalaemia (potassium 3.0–3.5 mmol/L) and 11 with mild hypomagnesia (magnesium 0.49–1.1 mmol/L). Troponin was ordered for 302 (47.7%) patients, many of whom had no history or risk factors for cardiac disease, or ischaemic symptoms associated with their SVT. The troponin was normal, mildly and moderately elevated in 65.2, 24.5 and 10.2% of cases, respectively. Only seven (1.1%) patients were diagnosed with acute myocardial ischemia. Although 190 (30.0%) patients had a chest X‐ray (CXR), it was normal in 78.4% of cases. All CXR abnormalities were incidental and not relevant to the immediate ED management. Conclusion: Patients with uncomplicated SVT are over‐investigated. Guidelines for ED SVT investigation are recommended. Further research is recommended to determine the indications for each investigation in the setting of SVT.